Treatment of selected Halogenated Organic Compounds in Water using Colloidal Silver Nanocatalysts under Reducing Borohydride Conditions - Adan , Tadicha; Victor Wandera , Opondo; Aloice , Ogweno; Ali , Shee (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Halogenated organic compounds (HOCs) are frequently encountered water contaminants. They are widely used as solvents or feed stocks in the production of paints, adhesives, lacquerers, pharmaceuticals and veterinary drugs, cosmetics, pesticides and herbicides. Most HOCs are recalcitrant, toxic and possible carcinogens. HOCs treatment in water may involve physical, biological and chemical processes. Chemical treatment via oxidation or reduction processes are preferred due to their ability to transform HOCs into environmental benign products. Compared to reduction, oxidation may produce toxic byproducts and thus for complete mineralization, huge amounts of redox equivalents are needed. Reductive dehalogenation is selective and more suited for HOCs treatment. It may employ electrocatalysts, metal catalysts and reagents. Nanoscale zero valent iron (nZVI) as an electron-releasing reagent is environmentally compatible but ineffective for transformation of saturated aliphatic HOCs containing
Keywords: Colloidal silver nanocatalysts, Halogenated organic compounds, Reductive dehalogenation, Sodium borohydride, Water treatment